Antibacterial Treatment Needed for Severe Early Childhood Caries - Ling Zhan, DDS, PhD; John D.B. Featherstone, MSc, PhD; Stuart A. Gansky, DrPH (Blackwell Synergy, 2006)
To assess the effects of a single 10% povidone iodine application as an adjunct to extensive surgical procedures in the clinical treatment of children with early childhood caries.